USING MATCHING GAMES IN BUILDING ELEMENTARY SCHOOL STUDENTS’ THREE-LETTER WORD ENGLISH VOCABULARY - Marpaung, Tiarma; Mesah, Murni Yunita; Tanu, Estaya; Taneh, Vebi Ari Yunita; Eky, Sepy Solitha (English Education Study Program - Artha Wacana Christian University, 2024)
As the basis of learning language skills, vocabulary mastery plays a crucial role. For students to understand and produce the language, they should have sufficient vocabulary knowledge and other language components to express their thoughts, feelings, and ideas. To accommodate students in mastering the target vocabulary, a word-matching game was used to help students learn vocabulary learning and acquisition. To do so, a classroom action research was conducted. The research took 27 students as the research participants. They were in their third grade of primary school. A pre-test and two post-tests were conducted to evaluate students’ vocabulary mastery in two cycles of the classroom action research. Students gained 17.29 of the average score in the pre-test with only 7 % of students being excellent, then improved the score in post-test 1 by 61.03 with 15% of the students getting excellent results, and got an even higher score in post-test 2 by 79.17 with 53% of them got an excellent score. By using the word-matching game technique, students' vocabulary mastery has shown significant improvement.